Aged-related changes in 2-AG metabolism enzymes expression and activity in rat cerebral cortex - Pascual, Ana Clara (2012)
Endocannabinoid 2-arachidonoylglycerol (2-AG) is synthesized by the enzymes diacylglycerol lipase (DAGL) and lysophosphatidate phosphohydrolase (LPAase). Its hydrolysis is carried out by monoacylglycerol lipase (MAGL) although other enzymes, such as fatty acid amide hydrolase (FAAH) and serine hydrolase ABHD may also be involved. The aim of this study was to analyze 2-AG synthesis and hydrolysis during physiological aging. Cerebral cortex membrane and soluble fractions; and synaptosomes from adult (3 mo) and aged (28 mo) rats were isolated by differential centrifugation and the synaptosomes were purified in ficoll gradients. LPAase, DAGL, and MAGLactivities were assayed using radiolabeled substrates, and their products were quantified from aqueous or lipid phase, previously separated by TLC. The expression of DAGL, MAGL and FAAH was analyzed by Western Blot. Both DAGL and ß were expressed in membranes while the second was only expressed in synaptosomes. The expression and activitiy of DAGL changed during aging. 2-AG hydrolysis showed no changes in the membrane fraction during aging in coincidence with the absence of changes in MAGL expression. 2-AG hydrolysis was observed to be higher in synaptosomes whereas MAGL expression decreased during aging. Our results show that the expression and activity of the enzymes involved in 2-AG metabolism are differently modulated by aging.